IgE class switch recombination is regulated by CaMKII via NF-κB alternative pathway. Issue 6 (2016) - Tanabe, Kano; Goto, Akihiro; Maeda, Akane; Sakamoto, Hitomi; Kajihara, Ryutaro; Fukunaga, Kohji; Inui, Seiji
No abstract available